Dual antiplatelet therapy following percutaneous coronary intervention: protocol for a systematic review - Elliott, Jesse (BMJ Open, 2019)
INTRODUCTION: Dual antiplatelet therapy (DAPT) is routinely given to patients after percutaneous coronary intervention (PCI) with stenting; however, there is ongoing debate about the optimal duration, especially in specific patient groups. In the proposed systematic review, we intend to assess the optimal duration of DAPT following PCI with stenting, with a focus on clinically relevant patient subgroups. METHODS AND ANALYSIS: We will perform a comprehensive search of the published literature for randomised controlled trials (RCTs) assessing the benefits and harms of extended DAPT (>12 months) compared with short-term DAPT (6–12 months) following PCI with stenting (bare metal or drug eluting). ClinicalTrials.gov and ICTRP will also be searched to identify ongoing and completed clinical trials. Two independent reviewers will select studies for inclusion, and the risk of bias will be assessed by use of Cochrane’s Risk of Bias tool. The primary outcome of interest is death (all-cause, cardiovascular, non-cardiovascular). Secondary outcomes are bleeding (major, minor, gastrointestinal), urgent target vessel revascularisation, major adverse cardiovascular events, myocardial infarction, stroke and stent thrombosis. Subgroup data will be sought for patients with prior myocardial infarction, acute coronary syndrome at presentation and diabetes, and based on smoking status and age group. Data will be analysed by random-effects meta-analysis, and separate analyses will be performed for patient subgroups. Bayesian network meta-analysis will be performed to investigate the effect of individual P2Y12 inhibitors at different DAPT durations longer than 6 months. ETHICS AND DISSEMINATION: This review will provide a comprehensive overview of the available evidence of the benefits and harms associated with extending DAPT beyond 12 months following PCI with stenting and the effects on clinically important subgroups. The results of this review will inform clinical and policy decisions regarding the optimal treatment duration of DAPT following PCI with stenting. SYSTEMATIC REVIEW REGISTRATION: PROSPERO no. CRD42018082587